Secret window - Polone, Gavin; Koepp, David; Depp, Johnny; Turturro, John, 1957-; Bello, Maria, 1967-; Hutton, Timothy, 1960-; Dutton, Charles S.; Cariou, Len.; Murphy, Fred.; Savitt, Jill.; Glass, Philip; Gadoury, Odette; et al. (Culver City, Calif. : Columbia TriStar Home Entertainment, 2004)
Following a bitter separation from his wife, famed mystery writer Mort Rainey is unexpectedly confronted at his remote lake house by a dangerous stranger named John Shooter. Claiming Mort has plagiarized his short story, the psychotic Shooter demands justice. When Shooter's demands turn to threats, and then to murder, Mort turns to a private detective he knows. But when nothing stops the horror from spiraling out of control, Mort soon discovers he can't trust anyone or anything.
Based upon the story "Secret window, secret garden" by Stephen King.
Special features: four deleted scenes (two deleted scenes include optional commentary with director David Koepp); director David Koepp's commentary; "From book to film" featurette; "A look through it" featurette; "Secrets revealed" featurette; animatics storyboards: opening credits, pushing car off cliff, twist revealed, into the garden; bonus trailers.
Director of photography, Fred Murphy ; editor, Jill Savitt ; music, Philip Glass ; costume designer, Odette Gadoury ; production designer, Howard Cummings.
Johnny Depp, John Turturro, Maria Bello, Timothy Hutton, Charles S. Dutton, Len Cariou.
MPAA rating: PG-13; for violence/terror, sexual content, language.
DVD, Region 1, widescreen presentation; Dolby Digital, DTS, SDDS.
Keywords: Authors -- Drama; Plagiarism -- Drama; Psychopaths -- Drama; Feature films; Thrillers (Motion pictures); Video recordings for the hearing impaired